Association between serum indoxyl sulfate levels with carotid-femoral pulse wave velocity in patients with chronic kidney disease. Issue 1 (1st January 2021) - Wang, Sheng-Chao; Lai, Yu-Hsien; Liu, Chin-Hung; Wang, Chih-Hsien; Hsu, Bang-Gee; Tsai, Jen-Pi
Abstract: Background: The role of indoxyl sulfate (IS), an important protein-bound uremic toxin, in arterial stiffness (AS) in patients with chronic kidney disease (CKD) is unclear. Materials and methods: We investigated the association between serum IS levels and AS in a cross-sectional study of 155 patients with CKD. Patients in the AS group was defined as carotid-femoral pulse wave velocity (cfPWV) value >10 m/s measured by a validated tonometry system (SphygmoCor), while values ≤10 m/s were regarded as without AS group Serum IS was measured by liquid chromatography–mass spectrometry analysis. Results: Of these CKD patients, AS was present in 51 (32.9%) patients, who were older, had a higher rate of diabetes, higher systolic blood pressure (SBP), and higher IS levels compared to those without AS. By multivariable logistic regression analysis, IS (adjusted odds ratio [aOR] 1.436, 95% confidence interval [CI] 1.085–1.901, p = 0.011), age (aOR 1.058, 95% CI 1.021–1.097, p = 0.002), and SBP (aOR 1.019, 95%CI 1.000–1.038, p = 0.049) were independent predictors of AS. By multivariable stepwise linear regression analysis, logarithmically transformed IS, age, DM, and SBP were significantly correlated with cfPWV. The area under the receiver-operating characteristic curve for serum log-IS was 0.677 (95%CI 0.598–0.750, p = 0.0001) to predict the development of AS in patients with CKD. Conclusion: These finding demonstrate that in addition to older and higher SBP, a high serum IS level is a significant biomarker associated with AS in patients with CKD.